2014
DOI: 10.1248/bpb.b13-00560
|View full text |Cite
|
Sign up to set email alerts
|

Effect of β-Cyclodextrin Derivatives on the Diosgenin Absorption in Caco-2 Cell Monolayer and Rats

Abstract: Orally administrated diosgenin, a steroidal saponin found in the roots of Dioscorea villosa, improves reduced skin thickness in ovariectomized mice, and plays an important role in the treatment of hyperlipidemia. Diosgenin has been noticed as an active element in cosmeceutical and dietary supplements. We have already elucidated that the absolute oral bioavailability of diosgenin is very low; however, a high skin distribution of diosgenin was also observed. The aim of the present study was to examine and compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 19 publications
0
14
0
Order By: Relevance
“…Moreover, the LC-MS technique was used for bioavailability studies of diosgenin in inclusion complexes with cyclodextrins in Caco-2 cell monolayers and rat jejunum. Interestingly, bioavailability of diosgenin in the presence of β -cyclodextrin derivatives was near 4- to 11-fold higher than that of diosgenin suspension [135]. The same research group evaluated, again by using LC-MS, the effect of diosgenin liquid crystals combined with cyclodextrin to increase the bioavailability of this steroid, after oral administration to rats [136].…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, the LC-MS technique was used for bioavailability studies of diosgenin in inclusion complexes with cyclodextrins in Caco-2 cell monolayers and rat jejunum. Interestingly, bioavailability of diosgenin in the presence of β -cyclodextrin derivatives was near 4- to 11-fold higher than that of diosgenin suspension [135]. The same research group evaluated, again by using LC-MS, the effect of diosgenin liquid crystals combined with cyclodextrin to increase the bioavailability of this steroid, after oral administration to rats [136].…”
Section: Methodsmentioning
confidence: 99%
“…The peak level of DG in the skin was observed at 6 h after oral administration. The plasma concentration of an orally administered DG reached C max (132:5 ± 48:2 ng/mL) at 5:01 ± 0:55 h with an AUC of 4121:9 ± 1354:7 ng • h/mL and an absolute oral bioavailability of 4:45 ± 1:46% [32,33]. Similarly, Liu et al have demonstrated that treatment with DG resulted in a C max of 42:1 ± 30:4 ng/mL at 11:3 ± 3:9 h along with an AUC 0-60 h of 1309:3 ± 849:8 ng h/mL and t 1/2 of 10:4 ± 4:2 h [48].…”
Section: Bioavailability and Pharmacokinetic Studies Of Diosgeninmentioning
confidence: 96%
“…However, DG is destabilized when it is exposed to hydrochloric acid [31]. DG is strongly hydrophobic (with Log P = 5:7), and it is insoluble in water [32,33]. The solubility of DG is around 0.7 ng/mL in aqueous medium [34].…”
Section: Chemistry Of Diosgeninmentioning
confidence: 99%
“…The aqueous solubility of DG was determined to be 0.7 ng/ml (1.69 nm). [9] It was also revealed that the low solubility of DG led to poor bioavailability and gastrointestinal mucosal toxicity. [10] As poor solubility has been recognized as a frequently encountered challenge in the field of pharmaceutics, different approaches have been employed to improve the solubility and bioavailability of poorly watersoluble compounds including DG.…”
Section: Introductionmentioning
confidence: 99%